ANALISIS PERSEPSI DAN KEBIJAKAN MANAJER RUMAH SAKIT TERHADAP UNDANG-UNDANG NO.44 RUMAH SAKIT PASAL 29 TENTANG KAWASAN TANPA ROKOK DI RUMAH SAKIT KABUPATEN SERDANG BEDAGAI - Damanik, Dady Hidayah; ., Juanita; BZ, Heldy (Jurnal Kesehatan Ilmiah Aufa Royhan, 2016)
Smoking bans hospital is intended to protect people (passive smokers) in a hospital from bad smoking habit and the hindrance of cigarette smoke and to create a hospital environment which is clean, healthful, and free from cigarette smoke.The objective of this qualitative research was to analyze manager’s perception and the policy of hospital management on the Hospital Law No. 44 on Smoking Bans Hospital of Serdang Bedagai District. The data were gathered by conducting in-depth interview. There were 22 informants in the research.The result of the research showed that all managers of the hospitals in Serdang Bedagai District had positive perception on Hospital Law No 44 on Smoking Bans Hospital and supported and wanted to implement the idea of smoking bans hospital. They stated that some factors which impeded the implementation of smoking bans were the personnel, patients, and patients’ families who had the habit of smoking. The commitment and the strict policy of the hospital and the government are the solution of these impeding factors in order that smoking bans can be implemented in every hospital.